World history as the history of foundations, 3000 BCE to 1500 CE - Borgolte, Michael, (Handbook of Oriental Studies. Section 1 The Near and Middle East;, 2020)
"In World History as the History of Foundations, 3000 BCE to 1500 CE, Michael Borgolte investigates the origins and development of foundations from Antiquity to the end of the Middle Ages. In his survey foundations emerge not as mere legal institutions, but rather as "total social phenomena" which touch upon manifold aspects, including politics, the economy, art and religion of the cultures in which they emerged. Cross-cultural in its approach and the result of decades of research, this work represents by far the most comprehensive account of the history of foundations that has hitherto been published".